Analysis of tool wear, surface roughness and cutting power in the turning process of compact graphite irons with different titanium content - Rosa,Sílvia do Nascimento (2010)
Due to its good mechanical properties, the Compacted (Vermicular) graphite cast iron (CGI) has found a lot of applications in the automobilistic field. One of the applications is the production of high power diesel engine blocks that, due to the higher strength compared to the usual gray cast iron, allows the increase of the pressure inside the cylinder and, consequently, production of high level of energy. The result is the better fuel burning what decreases the fuel consumption and the pollutants' emission levels. However, when CGI replaces gray cast iron, the machining processes used to produce the components are more difficult, with lower tool lives and higher power consumption. Moreover, because usually the raw material to produce cast products of CGI is selected from scrap, some residual level of titanium is present. Thus, the goal of this work is to study the influence of the titanium content (in residual levels) in the turning operation performance with carbide tools, using two cutting speeds. The results show that the alloys with the highest titanium content generated the shortest tool life, but the titanium content influenced neither power consumption nor workpiece surface roughness. Attrition/adhesion was the main tool wear mechanisms verified in this work.